MENGURAI KECANTIKAN BAHASA AL-QUR'AN: ANALISIS MENDALAM TERHADAP MAJAZ MURSAL ALAQAH JUZ’IYAH. - -, Murdiono90; Taufiq, Hadi Nur (AL MUALLAQAT, 2024)
This research aims to analyze the use of Majaz Mursal Alaqah Juz'iyyah in the Quran through the approach of Quranic Balaghah Studies. Qualitative methods are employed to explore and understand the meaning of Majaz Mursal in the context of Quranic Balaghah. The research population consists of Quranic verses containing Majaz Mursal Alaqah Juz'iyyah, with samples selected based on specific criteria. The results indicate that Majaz Mursal Alaqah Juz'iyyah is wisely utilized in the Quran, opening new dimensions of understanding divine messages. For example, in Surah Al-Lahab, the use of the term "Yadaa" (both hands) not only literally refers to the physical aspect but also creates symbolism for the power and actions supporting injustice by Abu Lahab. In Surah An-Nas, Majaz Mursal Juz'iyyah conveys the complexity of the hidden threat of Satan using the term "Alwaswasil Khannas." The research concludes that Majaz Mursal Alaqah Juz'iyyah in the Quran unveils profound layers of understanding and imparts nuances of wisdom. This study delves into the intricacies of Quranic Balaghah, providing new insights into the richness of meanings within the Islamic holy book